Pemanfaatan Rotan di Wilayah SUB DAS Mandar (Studi Kasus : Desa Kalumammang Kecamatan Alu) - Demma Semu, Yulsan; Sumarlin (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2024)
The aim of this study; to find out the use of rattan in the Mandar Sub-watershed, Kalumammang Village, Alu District, Polewali Mandar Regency. The use of rattan as a multi-purpose plant in the Mandar Sub-Watershed of Kalumammang Village has quite a lot of potential where there are 4 types of rattan. The rattan plants most widely used for woven materials are emblem (Calamus sp) and Sega rattan (Calamus axillaris Becc.). The types of rattan crafts used by the community include baskets used as containers for transporting goods and clothing containers, these baskets are made from sega rattan. Apart from that, there is also a mattress beating craft, which is woven material made from sega rattan which is usually used to beat mattresses after drying them so they don't get dusty. The traditional use of rattan is local wisdom that has been passed down from generation to generation, but there has been no research regarding the use of rattan as a craft material. Keywords: Utilization, rattan, types of crafts